Systemic Sclerosis: Pathogenesis, Diagnosis, and Management (Canadian Dermatology Today, 2024)
Systemic sclerosis (SSc) is an autoimmune fibrosing disease with internal organ involvement leading to significant morbidity and mortality. The average age of diagnosis ranges from 33.5–59.8 years with a strong female predominance (3.8–15 times more common).